The Development of a Questionnaire on Factors Affecting Non Adherence Behavior among Indonesian Elderly Population - Makkulawu, Andi; Setiadi, Adji Prayitno; Rahardjo, Tri Budi Wahyuni; Setiawan, Eko (UI Scholars Hub, 2018)
Instruments which can be used to identify factors affecting the medication adherence of elderly with diabetes mellitus (DM) have not been discovered in Indonesia. The objective of this study was to develop a questionnaire to identify factors affecting elderly patients’ medication adherence. The development of the questionnaire was conducted based on published references attained through the exploration of research evidence with several keywords and databases. Content validity was conducted using experts’ assessment (two experts). Face validity was conducted in 13 subjects including seven (7) non-elderly subjects and six (6) elderly subjects. Construct validity test was conducted based on calculated R against table R while reliability test was conducted with Cronbach’s Alpha. There were 30 elderly subjects included in the construct validity. Present study produced a valid and reliable questionnaire comprising 35 questions in 14 subcategories from 4 factor domains with the calculated R = 0.357-0.788 and Cronbach’s Alpha = 0.934. The questionnaire can be used for further research throughout Indonesia. Hence, a complete overview of factors affecting elderly DM patients’ medicine consumption adherence can be obtained. The identification of factors related to the usage of DM patients’ medicine is expected to serve as a base for the government, both of state and local government, to produce policies related to health interventions to be implemented.